Resisting reality social construction and social critique - Haslanger, Sally Anne. (Oxford : Oxford University Press, 2013)
In this collection of previously published essays, Sally Haslanger draws on insights from feminist and critical race theory and on the resources of contemporary analytic philosophy to develop the idea that gender and race are positions within a structure of social relations. Explicating the workings of these interlocking structures provides tools for understanding and combatting social injustice.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Social constructionism; Critical theory; Feminism; Social sciences -- Philosophy